Monday Night mayhem [videorecording (DVD)] - Turturro, John, 1957-; Heard, John, 1946-2017; Anderson, Kevin, 1960-; Turturro, Nicholas (Warner Home Video, 2002)
The story behind the early years of Monday Night Football and its sportscasting team of Howard Cosell, Frank Gifford and Don Meredith.